SOLUSI PERSAMAAN DIOPHANTINE DENGAN IDENTITAS BILANGAN FIBONACCI DAN BILANGAN LUCAS - puspitasari, Ayu; Sumanto, YD; Widowati, Widowati (MATEMATIKA, 2017)
In this paper we propose diophantine equations with the form Â and . These equations has integer solutions which can form Fibonacci numbers and Lucas numbers. Integer solutions of the Diophantine equations in the form of Fibonacci number and Lucas number are determined by using recursive formula, Binetâ€™s Formula, and the most important is identity of Fibonacci numbers and Lucas numbers.